Art Pedagogy for Self-assessment of Kindergarten Teachers (Journal of Educational Sciences, 2022)
The kindergarten teacher is both a teacher and an inspirer. The condition of his personal and professional effectiveness is stability associated with the balance of self-esteem. The aim of the study is togeneralize the innovative teaching experience, analyze and draw attention to an important personalconstruct – self-esteem of a kindergarten teacher as the basis for successful interaction and confidencein personal and professional terms. The article discusses the practical possibilities of self-assessment ofkindergarten teachers by means of art pedagogy. Known are the incentives of art to change and the motivation of the individual to achieve. Art pedagogy differs from conventional methods of education andupbringing, and involves direct creative interaction between its subjects. The technological feature ofart pedagogy is game methods and improvisation, which are non-standard ways of self-expression andmotivation in the process of work. The article reveals art methods such as the exercises “Coefficient ofSpiritual Intelligence”, “My multi-colored name” and others. The presence of spiritual intelligence allowsyou to show creativity, flexibility and the ability to transform the rules. It is the capacity for compassionand the moral code, the capacity for evaluation and the mood for change, it promotes dialogue betweenthe mind and the sensesKey words: art pedagogy, self-assessment, educator, kindergarten.